Highly Durable Platinum Single‐Atom Alloy Catalyst for Electrochemical Reactions. Issue 1 (11th September 2017) - Kim, Jiwhan; Roh, Chi‐Woo; Sahoo, Suman Kalyan; Yang, Sungeun; Bae, Junemin; Han, Jeong Woo; Lee, Hyunjoo
Abstract: Single atomic Pt catalyst can offer efficient utilization of the expensive platinum and provide unique selectivity because it lacks ensemble sites. However, designing such a catalyst with high Pt loading and good durability is very challenging. Here, single atomic Pt catalyst supported on antimony‐doped tin oxide (Pt1/ATO) is synthesized by conventional incipient wetness impregnation, with up to 8 wt% Pt. The single atomic Pt structure is confirmed by high‐angle annular dark field scanning tunneling electron microscopy images and extended X‐ray absorption fine structure analysis results. Density functional theory calculations show that replacing Sb sites with Pt atoms in the bulk phase or at the surface of SbSn or ATO is energetically favorable. The Pt1/ATO shows superior activity and durability for formic acid oxidation reaction, compared to a commercial Pt/C catalyst. The single atomic Pt structure is retained even after a harsh durability test, which is performed by repeating cyclic voltammetry in the range of 0.05–1.4 V for 1800 cycles. A full cell is fabricated for direct formic acid fuel cell using the Pt1/ATO as an anode catalyst, and an order of magnitude higher cell power is obtained compared to the Pt/C. Abstract : Platinum single‐atom alloy is prepared on an antimony‐doped tin oxide support (Pt1/ATO) and used for electrochemical formic acid oxidation with high activity and durability. The single atomic nature of Pt is retained even after the durability test performed by repeating cyclic voltammetry 1800 times in 0.05–1.4 V.